Intracerebroventricular Ghrelin Administration Increases Depressive-Like Behavior in Male Juvenile Rats - Jackson, Thomas M.; Ostrowski, Tim D.; Middlemas, David S. (Frontiers in Behavioral Neuroscience, 2019)
Major Depressive Disorder (MDD) is arguably the largest contributor to the global disease and disability burden, but very few treatment options exist for juvenile MDD patients. Ghrelin is the principle hunger stimulating peptide, and it has also been shown to reduce depressive-like symptoms in adult rodents. We examined the effects of intracerebroventricular (icv) injections of ghrelin on depressive-like behavior. Moreover, we determined whether ghrelin increased neurogenesis in the hippocampus. Ghrelin (0.2-nM, 0.5-nM, and 1.0-nM) was administered acutely by intracerebroventricular (icv) injection to juvenile rats to determine the most effective dose (0.5-nM) by a validated feeding behavior test and using the forced swim test (FST) as an indicator of depressive-like behavior. 0.5-nM ghrelin was then administered icv against an artificial cerebrospinal fluid (aCSF) vehicle control to determine behavioral changes in the FST and the tail suspension test (TST) as indicators of depressive-like behavior. Neurogenesis was investigated using a mitogenic paradigm, as well as a neurogenic paradigm to assess whether ghrelin altered neurogenesis. Newborn hippocampal cells were marked using 5’-bromo-2’-deoxyuridine (BrdU) administered intraperitoneally (ip) at either the end or the beginning of the experiment for the mitogenic and neurogenic paradigms, respectively. We found that acute ghrelin administration increased immobility time in both the FST and the TST. Treatment with ghrelin did not change mitogenesis or neurogenesis. These results suggest that acute ghrelin administration does not effectively reduce depressive-like symptoms; in contrast to adult rodents, ghrelin increases depressive-like behavior in male juvenile rats. These results highlight the need to better delineate differences in the neuropharmacology of depressive-like behavior between juvenile and adult rodents.